Interaction of the Aspergillus nidulans Microtubule-Organizing Center (MTOC) Component ApsB with Gamma-Tubulin and Evidence for a Role of a Subclass of Peroxisomes in the Formation of Septal MTOCs - Zekert, Nadine (American Society for Microbiology, 2010)
Peroxisomes are a diverse class of organelles involved in different physiological processes in eukaryotic cells. Although proteins imported into peroxisomes carry a peroxisomal targeting sequence at the C terminus (PTS1) or an alternative one close to the N terminus (PTS2), the protein content of peroxisomes varies drastically. Here we suggest a new class of peroxisomes involved in microtubule (MT) formation. Eukaryotic cells assemble MTs from distinct points in the cell. In the fungus Aspergillus nidulans, septum-associated microtubule-organizing centers (sMTOCs) are very active in addition to the spindle pole bodies (SPBs). Previously, we identified a novel MTOC-associated protein, ApsB (Schizosaccharomyces pombe mto1), whose absence affected MT formation from sMTOCs more than from SPBs, suggesting that the two protein complexes are organized differently. We show here that sMTOCs share at least two further components, gamma-tubulin and GcpC (S. pombe Alp6) with SPBs and found that ApsB interacts with gamma-tubulin. In addition, we discovered that ApsB interacts with the Woronin body protein HexA and is targeted to a subclass of peroxisomes via a PTS2 peroxisomal targeting sequence. The PTS2 motif was necessary for function but could be replaced with a PTS1 motif at the C terminus of ApsB. These results suggest a novel function for a subclass of peroxisomes in cytoskeletal organization.